From Cash to Clicks: The Impact of Touch’n Go on Student Financial Behaviors - Kaim, Sakshi; Kean, Koay Loke; Binti Ahmad Khairul, Aeisyah; Binti Tarmidzi, Nurfarhani; Binti Sulaiman, Nurul Asyikin; Binti Shamsul Anuar, Nurfarah Alya; Binti Anuar, Nurdini; Kee, Daisy Mui Hung (Advances in Global Economics and Business Journal, 2024)
This study investigates the impact of transitioning from cash transactions to digital payment methods, specifically focusing on the Touch'n Go system, on the student's financial behaviors. With the proliferation of digital payment technologies, understanding how such transitions affect financial habits is essential for both academic and industry. Through a mixed-methods approach involving surveys and interviews, this research explores various dimensions of student financial behaviors, including spending patterns, budgeting practices, saving habits, and financial literacy. The findings contribute to the existing literature on digital finance and provide insights for policymakers, educators, and financial institutions aiming to support the financial well-being of young adults in an increasingly digital economy. With the advancement of technology and implementation of the fourth industrial revolution, digital wallet payment methods have appeared as the latest wave in the market. People can now enjoy cashless payments with a simple tap of a button. Due to the Covid-19 pandemic, digital wallet use among consumers significantly increased. The study was conducted to analyze the impact of using digital payment influenced students behaviour. To explore, the collection of both primary and secondary data is done through several sources, and a digital questionnaire was produced to collect data and information from respondents. The result indicated that perceived usefulness, perceived product features, perceived convenience, perceived security and customer satisfaction of the Touch 'n Go E-wallet application significantly influence Student behavioral intention using the e-wallet payment method